Diastolic dysfunction worsen prognosis in patients with dilated cardiomyopathy independently of left ventricular systolic dysfunction. (4th February 2022) - Dziewiecka, E; Winiarczyk, M; Karabinowska, A; Gliniak, M; Robak, J; Kaciczak, M; Wisniowska-Smialek, S; Rubis, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The heart failure (HF) symptoms and prognosis in patients with HF with reduced ejection fraction (LVEF; HFrEF) is mostly associated with left ventricle (LV) remodelling and systolic dysfunction. However, in HFrEF patients the LV diastolic function is usually also impaired and worsen the prognosis. The significance of LV dysfunction in dilated cardiomyopathy (DCM) is well recognised, but not the diastolic dysfunction. Aim: The analysis of diastolic function in DCM with different systolic impairment and its impact on the prognosis. Methods: Between 2010 and 2020 we retrospectively analysed out- and in-hospital records of 567 DCM patients (age 52 ± 13 years, 78% male, NYHA 2.4 ± 0.8) with complete echocardiographic and outcome data. Patients were divided into 3 groups based on LVEF (EF1 <20%, EF2 20-29%, EF3 ≥30%) and into 3 groups according to diastolic function based on the ASE/EACVI 2016 recommendations. Results: Most patients had no or mildly impaired diastolic function, however nearly 50% of EF1 patients had abnormal diastolic function (Table 1). During observation of 41 ± 27 months, 88 (16%) patients died (Table 1). Impaired diastolic function (G2 or G3) was found to be significant prognostic factor independently of LVEF (G2-3: HR 2.44 [95%CI 1.59-3.70], p < 0.001; LVEF: HR 0.10 [95%CI 0.09-0.10] for every 10%, p = 0.002) (Figure 1). Conclusion: Most DCM patients had severely impaired LV systolic function and no or mildly impaired diastolic function. In DCM patients the diastolic dysfunction significantly worsens the prognosis independently of LVEF.